THE INFLUENCE OF SKEPTISM, AND TIME PRESSURE ON THE AUDITOR'S ABILITY TO DETECT FRAUD WITH THE AUDITOR'S EXPERIENCE AS A MODERATION VARIABLE - Lilyana, Lilyana; Kartini, Kartini; T. Pontoh, Grace (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
This research analyzes influence skepticism professional , and pressure time to internal auditor capabilities detect fraud with experience as variable moderation . This research uses office auditors accountant public (big four) as subject study with amount sample a total of 240 auditors were determined with using purposive sampling. This research uses primary data, where method data collection is carried out with do spread questionnaire . Statistical methods used​ For test hypothesis is with using Structural Equation Model (SEM). Research results shows (1) Skepticism influential positive and significant to auditor's ability to detect cheating . (2) Pressure time influential negative to auditor's ability to detect cheating . (3) Experience strengthen in moderate influence skepticism to auditor's ability to detect cheating . and (4) Experience strengthen in moderate influence pressure time to auditor's ability to detect cheating. Currently still lack of study about connection these variables with use the role of the office auditor accountant public big four as subject his research . This research also provides contribution theory with give understanding about How practice skepticism , pressure time can influence Fraud detection by an auditor , especially auditors who work in offices accountant public big four . Keywords: Skepticism, Pressure Time, Experience, Detect Cheating